Parenteral Antioxidant Supplementation at Birth Improves the Response to Intranasal Vaccination in Newborn Dairy Calves - Arpita Nayak; Angel Abuelo (MDPI AG, 2021)
Newborn calves experience oxidative stress throughout the first month of their life, which is known to decrease lymphocyte functions relevant to vaccine responsiveness. Thus, this study aimed to determine the extent to which parenteral antioxidant supplementation given at birth improves the response to an intranasal viral vaccine in the first month of life of newborn dairy calves. For this, 21 calves were randomly assigned at birth to one of two commercially available antioxidant micronutrient supplements or a placebo group receiving 0.9% sterile saline (n = 7/group). Serum and nasal secretion samples were collected before administration of treatments and an intranasal vaccine against respiratory viruses (bovine herpesvirus type 1, bovine syncytial respiratory virus, and parainfluenza 3), and once weekly for the first four weeks of age. Systemic redox balance was determined in serum. Immunoglobulin A specific for bovine herpesvirus 1 and bovine syncytial respiratory virus was quantified in nasal secretions as a proxy to intranasal vaccine responsiveness. Our results showed that parenteral administration of antioxidants at birth improved calves' redox balance. Additionally, calves receiving antioxidant supplementation had higher concentrations of immunoglobulin A in their nasal secretions than calves in the control group. Thus, we conclude that supplementation of calves with antioxidants at birth could be a practical strategy to improve intranasal vaccine response. Future larger studies should evaluate the extent to which this increased mucosal response to intranasal vaccination could result in decreased calf morbidity and mortality.